The Principles of Exchange Rate Determination in an International Finance Experiment - Noussair, Charles N.; Plott, Charles R.; Riezman, Raymond G. (Journal of Political Economy, 1997)
This paper reports the first experiments designed to explore the behavior of economies with prominent features of international finance. Two “countries,” each with its own currency, were created. International trade could take place only through the operation of markets for currency. The law of one price and the flow of funds theory of exchange rate determination were used to produce general equilibrium models that captured much of the behavior of the economies. Prices of goods, as well as the exchange rate, evolve over time toward the predictions of the models. However, both the law of one price and purchasing power parity can be rejected for reasons that do not appear in the literature. Patterns of international trade were as predicted by the law of comparative advantage.